Stabilizing decontamination foam using surface-modified silica nanoparticles containing chemical reagent: foam stability, structures, and dispersion properties. Issue 3 (6th January 2021) - Yoon, In-Ho; Yoon, Suk Bon; Sihn, Youngho; Choi, Man-Soo; Jung, Chong-Hun; Choi, Wang-Kyu
Abstract : The stabilization of decontamination foams containing a chemical reagent is a crucial requirement for their use in the decontamination of nuclear power plants. Abstract : The stabilization of decontamination foams containing a chemical reagent is a crucial requirement for their use in the decontamination of nuclear power plants. We have investigated the effects on decontamination foam stability of adding silica nanoparticles (NPs) modified with various functional groups, namely propyl (–CH3 ), amine (–NH2 ), and thiol (–SH) groups. The surface properties of these silica NPs were characterized with ATR-FTIR, solid NMR, and TGA analyses. We also established that the agglomeration in such foams of the amine-modified silica NPs is weaker than that of the other modified silica NPs due to their thorough dispersion in the liquid film. Further, the foam containing amine-modified silica NPs was found to be stable for 60 min at a pH of 2, i.e. under decontamination conditions. The bubble structure analysis showed that this decontamination foam has a bubble count that is approximately 5–8 times higher than the foams containing NPs modified with the other functional groups, which indicates that the decontamination foam with amine-modified silica NPs has the best foam structure of the three investigated foams. The well-dispersed and smaller amine-modified silica NPs enhance the foam stability by providing a barrier between the gas bubbles and delaying their coalescence. In contrast, the thiol- and propyl-modified silica NPs form aggregates with large diameters that reduce the maximum capillary pressure of coalescence and hence decrease the foam stability.